2016
DOI: 10.1063/1.4945571
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on emission and stability of dual feed biogas swirl combustor

Abstract: Biomass is a renewable energy source with the highest potential to contribute in meeting energy needs and providing a secure and sustainable energy supply. For combustion of biogas (low calorific gas), an efficient technology is needed. It should provide stable combustion with low emission of pollutants such as CO and NOx over a wide operating range. This paper presents the experimental investigation on emission and stability of a premixed dual feed biogas swirl combustor with a pilot burner. For the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…This was also confirmed by Liu et al [28]. Despite the deterioration of the biogas ignition and flame stability region associated with the presence of CO 2 , our experimentation and those of [45] have confirmed that appropriate use of a swirl combustor can stabilize the biogas flame over a wide range of equivalence ratios. The air swirl intensity of the designed combustor was high enough to stabilize the biogas flame, promising ignition and sustainable combustion.…”
Section: Lean Blow-off and Litsupporting
confidence: 88%
“…This was also confirmed by Liu et al [28]. Despite the deterioration of the biogas ignition and flame stability region associated with the presence of CO 2 , our experimentation and those of [45] have confirmed that appropriate use of a swirl combustor can stabilize the biogas flame over a wide range of equivalence ratios. The air swirl intensity of the designed combustor was high enough to stabilize the biogas flame, promising ignition and sustainable combustion.…”
Section: Lean Blow-off and Litsupporting
confidence: 88%